PENGELOLAAN SARANA PRASARANA DALAM PROSES PEMBELAJARAN DI MADRASAH IBTIDAIYAH UNTUK MENDUKUNG PENANAMAN KARAKTER - Pamuji, Zuri (JMIE (Journal of Madrasah Ibtidaiyah Education), 2022)
Management of infrastructure facilities plays an important role in supporting the success of the learning process, and every teacher should try to do it well. Especially if learning is not only directed in the context to mastering the material, but also as a means of internalisasing character in students. The research seeks to describe the management of infrastructure in supporting the learning process by the teacher in 1st grade at MI Darul Hikmah. Data collecting uses interview, observation and documentation. The results showed that the efforts made by the teacher included: first, taking an inventory of the facilities and infrastructure in the classroom. Second, arrange the infrastructure in the classroom, including the position of student desks and chairs. Third, linking the management of infrastructure facilities with the learning process to support character instilling in students, both in the planning, implementation and closing stages. And this gives a real impact in the learning process that is carried out